PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM KASUS PENCEMARAN LINGKUNGAN HIDUP MELALUI PENDEKATAN KEADILAN RESTORATIF - Darmawan, Iwan; Absar Kertabrata, (Journal of Innovation Research and Knowledge, 2026)
While environmental regulations in Indonesia address corporate criminal liability, widespread environmental pollution persists without effective ecosystem restoration. This article aims to explore the potential of a restorative justice approach as an alternative to conventional retributive sanctions for corporations. Employing a normative legal research method and a case study analysis of environmental pollution (Decision No. 856/Pid.B/LH/2021/PN Bdg), this study identifies the gap between criminal law enforcement and the objectives of environmental restoration. The research findings indicate that restorative mechanisms not only facilitate fairer corporate accountability but also ensure tangible environmental recovery through stakeholder engagement. This article concludes that integrating restorative justice into the environmental criminal law system is urgent to address the failures of the current system in achieving ecological justice